Regulation of Endothelial-to-Mesenchymal Transition by microRNAs in Chronic Allograft Dysfunction - Glover, Emily K. (Transplantation, 2019)
Fibrosis is a universal finding in chronic allograft dysfunction and is characterized by an accumulation of extracellular matrix. The precise source of the myofibroblasts responsible for matrix deposition is not understood and pharmacological strategies for prevention or treatment of fibrosis remain limited. One source of myofibroblasts in fibrosis is endothelial-to-mesenchymal transition, a process first described in heart development and involving endothelial cells undergoing a phenotypic change to become more like mesenchymal cells. Recently, lineage tracing of endothelial cells in mouse models allowed studies of EndMT in vivo and reported 27-35% of myofibroblasts involved in cardiac fibrosis and 16% of isolated fibroblasts in bleomycin-induced pulmonary fibrosis to be of endothelial origin. Over the last decade, miRNAs have increasingly been described as key regulators of biological processes through repression or degradation of targeted mRNA. The stability and abundance of miRNAs in body fluids makes them attractive as potential biomarkers and progress is being made in developing miRNA targeted therapeutics. In this review we will discuss evidence of miRNA regulation of EndMT from in vitro and in vivo studies and the potential relevance of this to heart, lung and kidney allograft dysfunction.